2016
DOI: 10.3109/09638288.2015.1111433
|View full text |Cite
|
Sign up to set email alerts
|

Coping strategies used by traumatic spinal cord injury patients in Sri Lanka: a focus group study

Abstract: Rehabilitation efforts for Sri Lankan SCI patients should be sensitive to psychosocial concerns in addition to physical concerns in order to help patients re-integrate into their family lives and community. Furthermore, religious practices should be respected as possible aids to rehabilitation. Implications for Rehabilitation Rehabilitative efforts should be conscientious of patients' psychosocial well-being in addition to their physical well-being. Hospital-based rehabilitative efforts for traumatic spinal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Our own qualitative work using focus groups revealed S/R practices to be mechanisms by which participants confront personal challenges following SCI. 8 Participants in our patient sample relied on S/R practices for comfort and consolation, and some believed that their S/R practices assisted them in improving their health condition. While our qualitative findings elucidate the importance of S/R towards our patient sample's overall coping, our quantitative findings specifically show that depressive symptoms in our patient population are inversely predicted by perceived benefit through S/R.…”
Section: Prevalence Of Depressive Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our own qualitative work using focus groups revealed S/R practices to be mechanisms by which participants confront personal challenges following SCI. 8 Participants in our patient sample relied on S/R practices for comfort and consolation, and some believed that their S/R practices assisted them in improving their health condition. While our qualitative findings elucidate the importance of S/R towards our patient sample's overall coping, our quantitative findings specifically show that depressive symptoms in our patient population are inversely predicted by perceived benefit through S/R.…”
Section: Prevalence Of Depressive Symptomsmentioning
confidence: 99%
“…Furthermore, patients frequently and almost unanimously reported that religious or spiritual practices aided them in confronting challenges posed by their injury. 8 Based on qualitatively identified psychosocial concerns associated with SCI and the strong recognition of religious practice as a coping mechanism in the Sri Lankan patient population, the quantitative aspect of this study was designed to assess specific potential predictors of depression. It was hypothesized that patients perceiving greater functional impairment in various life domains would be more likely to suffer from depression and that patients who identified greater benefit from spirituality/religiosity (S/R) would be less likely to suffer from depression.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, like other studies (Arya et al, 2016;Khanjani et al, 2017), social support from the family and members of the community is found to be one of the crucial coping resources for persons with TSCI. This could be explained by the fact that persons with TSCI need long-term emotional and physical support due to the physical abilities they have lost.…”
Section: Discussionmentioning
confidence: 77%
“…In poor, rural African settings, such assistance is normally provided by a spouse, family member or close relative. Various studies have shown that social support is a key facilitator of daily activities, mobility and overall quality of life for persons with SCI regardless of context (Arya et al, 2016;Khanjani, Younesi, Khankeh, & Azkhosh, 2017). Furthermore, support from close relatives and friends contributes to resilience, better physical and mental health, reduced pain, better coping, and greater satisfaction with life among persons with SCI (Bailey, Gammage, Ingen, & Ditor, 2015;Muller, Peter, Cieza, & Geyh, 2012;Muller et al, 2015;Zsoldos, Satori, & Zana, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A study on spinal cord injury patients in Sri Lanka has identified the need for culturally sensitive, practical rehabilitative programms focus on patients' psychological well-being for a speedy recovery. They further suggested that spiritual and religious practices be incorporated into rehabilitation and therapeutic interventions because religious participation is essential in improving the health and well-being of the patients (Arya et al, 2016). In Sri Lanka, a validated tool is not available to measure religious and spiritual support received or perceived by patients with chronic illnesses such as cancer.…”
Section: Literature Reviewmentioning
confidence: 99%